1999
DOI: 10.1007/s100380050161
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic forms of the protein L-isoaspartate (D-aspartate) O-methyltrans-ferase involved in the repair of age-damaged proteins

Abstract: The protein L-isoaspartate (D-aspartate) Omethyltransferase (PCMT1) can initiate the repair of agedamaged aspartyl and asparaginyl residues of intracellular proteins. The human gene PCMT1 encoding this enzyme has at least four polymorphic sites, one of which results in two major isoforms with either an Ile residue or a Val residue at amino acid position 119. The frequencies of the alleles encoding the Ile 119 and Val 119 variants are similar in Caucasian populations, but a predominance of the Ile 119 allele ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…These observed lowered risks suggest that the affinity for AdoMet by PIMT may play a more important role during neural tube closure in embryonic development than what is inferred simply by its specific activity. In vitro studies showed that the Ile/Ile genotype had 20% higher specific activity but 30% lower substrate affinity than Val/Val [12]. Our findings were consistent with DeVry's hypothesis that a 30% increase in substrate affinity in Val/Val genotype could account for a substantial decrease in damaged protein accumulation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These observed lowered risks suggest that the affinity for AdoMet by PIMT may play a more important role during neural tube closure in embryonic development than what is inferred simply by its specific activity. In vitro studies showed that the Ile/Ile genotype had 20% higher specific activity but 30% lower substrate affinity than Val/Val [12]. Our findings were consistent with DeVry's hypothesis that a 30% increase in substrate affinity in Val/Val genotype could account for a substantial decrease in damaged protein accumulation.…”
Section: Discussionsupporting
confidence: 90%
“…A complete linkage disequilibrium (LD) was observed between the two SNPs (rs4816 and rs4552) in both subpopulations (nonHispanic White and Hispanic white) in our study. This finding is in line with previously published work [12]. We further interrogated available SNP genotyping data in PCMT1 gene from www.hapmap.org [19], using Haploview 3.2 (http://www.broad.mit.edu/mpg/haploview) [20].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Some protein deamidation is subject to repair by the enzyme protein L-isoaspartate (Daspartate) O-methyltransferase (PCMT1). Polymorphism results in different human PCMT1 isoforms with either isoleucine or valine at position 119; these differ in specific activity and substrate affinity (De Vry & Clarke, 1999;Clarke, 2003). It appears that healthy aging may correlate with an increased frequency of a heterozygous genotype, simultaneously expressing both isoforms (Clarke, 2003).…”
Section: Biological Aging and Post-translational Protein Modificmentioning
confidence: 99%